Genetic variability of Herpailurus yagouaroundi, Puma concolor and Panthera onca (Mammalia, Felidae) studied using Felis catus microsatellites - Moreno, Vanessa Roma [UNESP]; Grisolia, Alexéia Barufatti [UNESP]; Campagnari, Francine [UNESP]; Milazzotto, Marcela [UNESP]; Adania, Cristina Harumi; Garcia, José Fernando [UNESP]; Souza, Edislane Barreiros de [UNESP] (Sociedade Brasileira de Genética, 2006)
We used four microsatellite loci (Fca08, Fca45, Fca77 and Fca96) from the domestic cat, Felis catus, to investigate genetic variability in specimens of Herpailurus yagouaroundi (jaguarundi, otter cat, eyra), Puma concolor (cougar, mountain lion, puma) and Panthera onca (jaguar) held in various Brazilian zoos. Samples of DNA from the cats were PCR amplified and then sequenced before being analyzed using the CERVUS program. Our results show a mean polymorphic information content (PIC) of 0.83 for H. yagouaroundi, 0.66 for P. concolor and 0.69 for P. onca and a mean of 10.3 alleles for the Fca08 locus, 5.3 for Fca 45, 9 for Fca 77 and 14 for Fca 96. These results indicate a relatively high level of genetic diversity for the specimens studied.
Keywords: genetic variability; mammals; felines; microsatellites